Secondary Chondrosarcoma of the Lumbosacral Region: Are any Bones Spared in the Multiple Hereditary Exostoses? - Anantharamaiah, Hemalatha (JCDR Research and Publications (P) Limited, 2012)
Osteochondromas are the most common benign bone tumors. Usually solitary, multiple osteochondromas (exostoses) are seen in patients with Multiple Hereditary Exostoses (MHE). Chondromatous transformation of lumbar osteochondroma in a patient with multiple exostoses is a rare phenomenon. We present a rare case of secondary chondrosarcoma of lumbar exostoses with patient presenting with symptoms of pain in the right lumbar region and paresis of right lower limb. Patients with multiple exostoses are prone to develop chondrosarcoma early in life. These patients need long term follow up with regular clinical and radiological examination.